Study of honey bee effect on melatonin concentration and many immunological and biochemical parameters in women suffering Chronic kidney disease in Kirkuk city - Wedad Mahmood L. Al-obaidi (Tikrit Journal of Pure Science)
The present study designed to demonstrate positive effect for honey bee on melatonin conc. and some immunological and biochemical parameters in women suffering Chronic kidney disease (CKD), the study include (55) blood samples get from women with CKD , (21) women from them volunteered to eat natural honey for thirty days, compared with (20) samples for normal women as control with age (20-49)year ,the samples were collected from Kirkuk hospital and clinicals from febreuary/2015 to june/2015.